Late Quaternary glacial history of the Nalati Range, central Tian Shan, China, investigated using Be-10 surface exposure dating - Zhang, Mei; Chen, Yixin; Li, Yingkui; Liu, Gengnian (Journal of Quaternary Science, 2016)
We constrained glacial chronologies in three valleys on the southern slopes of the Nalati Range in the central Tian Shan, China: the Takelakete, Aiken and Sairenwuxunsala valleys, using Be-10 surface exposure dating. Our Be-10 exposure ages constrain three glacial events during 72.8 +/- 3.8-59.9 +/- 3.5 ka, 55.4 +/- 3.0-34.9 +/- 2.1 and 0.29 +/- 0.17-0.27 +/- 0.20 ka, corresponding to Marine Oxygen Isotope Stages (MIS) 4 and 3, and Little Ice Age (LIA), respectively. Glaciers have been restricted from composite valley glaciers and piedmont glaciers during MIS 4-3 to confined valley glaciers during MIS 3, to small valley glaciers during the LIA, and to hanging and cirque glaciers at present. This pattern of glacial change is broadly consistent with other glaciated areas across the Tian Shan. Extensive glacial advances during MIS 4 and 3 were probably driven by enhanced precipitation brought by the westerlies. Compared to MIS 3 glacial advance, lower temperature may counteract the effect of relatively lower precipitation to drive a similar or even larger glacial advance during MIS 4. Glacial advances were limited during MIS 2, probably reflecting enhanced arid conditions in the Tian Shan caused by the weakened westerlies and strengthened Siberian High. Copyright (C) 2016 John Wiley & Sons, Ltd. National Natural Science Foundation of China [40971002, 41328001, 41371082, 41230743, 41101003] SCI(E) ARTICLE chenyixin@pku.edu.cn 7 659-670 31